Social Conditions In The Novel Frog Music By Emma Donoghue - Muhammad Ilham Ali (Journal of Cross Knowledge, 2024)
This study aims to find out the social conditions in the novel Frog Music by Emma Donoghue. This research used qualitative research. This research used a sociological approach to identify social conditions in the novel Frog Music by Emma Donoghue: the sociological theory and experience to go beyond everyday understandings of people and situations. The data were taken from all sentences as the content of the novel. There are two steps in collecting the data, namely reading and identifying. Based on the data analysis in the findings and discussion, it is concluded that in the novel Frog Music by Emma Donoghue, four social conditions appear: violence, striptease, virus, and heinous.